JCAD enhances arterial thrombosis by regulating endothelial plasminogen activator inhibitor-1 and tissue factor expression. (14th October 2021) - Liberale, L; Akhmedov, A; Bonetti, N R; Puspitasari, Y M; Vukolic, A; Montecucco, F; Beer, J H; Jin, Z G; Liuzzo, G; Stellos, K; Crea, F; Luscher, T F; et al.
Abstract: Introduction: Arterial thrombosis underlies most acute CV events. Variants of the Junctional cadherin 5 associated (JCAD) locus were consistently shown to associate with increased risk of acute coronary syndrome. Being a component of cell junctions, JCAD protein is highly expressed in endothelial cells and was shown to promote atherosclerosis by acting on the Hippo pathway through LATS2 kinase. Purpose: This project investigated the effect of JCAD in arterial thrombosis by using an established in vivo mouse model of carotid injury. The translational value of animal findings was assessed in primary human aortic endothelial cells (HAECs) as well as in CV patients. Methods: JCAD knock-out (Jcad−/−) mice were exposed to photochemically-induced carotid artery endothelial injury to trigger thrombosis. Primary HAECs treated with JCAD small-interfering RNA (si-JCAD), LATS2-silencing RNA (si-LATS2) or control siRNA (si-SCR) were employed for in vitro assays. Plasma JCAD was measured in patients with chronic coronary syndrome (CCS) or ST-elevation myocardial infarction (STEMI). Results: Compared to wild-type, Jcad−/− mice displayed reduced thrombus formation as underlined by delayed time to occlusion following endothelial-specific carotid damage. Suggesting a blunted activation of the extrinsic coagulation cascade, Jcad−/− animals showed reduced tissue factor (TF) protein expression and activity in carotid artery lysates (Fig. 1). Increased thrombus embolization episodes and D-dimer further suggested an increased activation of the fibrinolytic system in Jcad−/− mice. Indeed, Jcad−/− mice displayed reduced vascular expression of the fibrinolysis inhibitor plasminogen activator inhibitor (PAI)-1. In contrast, platelets aggregation in response to collagen and thrombin was similar in Jcad−/− and Jcad+/+ mice (Fig. 1). In line with the in vivo data, JCAD-silencing of HAECs inhibited TF and PAI-1 gene and protein expression. In accordance with previous literature, JCAD-silenced HAECs displayed increased levels of LATS2 Kinase, which blunts the Hippo pathway by increasing YAP phosphorylation. Yet, double JCAD and LATS2 silencing did not retrieve the phenotype of control HAECs. Of interest, si-JCAD HAECs showed increased levels of Akt phosphorylation, known to downregulate procoagulant expression and to directly phosphorylate YAP. Treatment with the Akt inhibitor Wortmannin prevented the effect of JCAD silencing on TF and PAI-1 indicating a causative role for this pathway (Fig. 2). Recapitulating in vitro findings, p-Akt and p-YAP levels were higher in arterial tissue of Jcad−/− animals as compared to WT (Fig. 1). Patients with STEMI showed significantly higher plasma levels of JCAD as compared to CCS (Fig. 2). Conclusions: JCAD promotes arterial thrombosis by selectively modulating coagulation and fibrinolysis, but not platelet aggregation through endothelial TF and PAI-1. Our findings support the importance of JCAD as a novel therapeutic target for CV prevention. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation